Colonial Development and Population in Taiwan - Barclay, George W. (Book collections on Project MUSE., 1954)
An unusual view of an agrarian region in the process of development by a colonial power. Taiwan (or Formosa), when it reverted to Chinese control in 1945, had been for fifty years the Japanese empire's most cherished foreign possession. Using the remarkable statistical data that the Japanese compiled to aid their administration-one of the most complete and creditable records for a population of this size that has ever been at the disposal of demographers-this book is able to present an authoritative picture of the social economic agricultural and demographic development of the island. Originally published in 1966. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.